Is government really solving the housing problem? - Toby C. Monsod (University of the Philippines, School of Economics (UPSE), 2011)
Informal housing arrangements, substandard structures, congestion, and land use conflicts characterize the urban housing problem in the Philippines. The record suggests that the response of the State, especially its reliance on below-market priced mortgage loans, has aggravated rather than helped solve the situation. If the housing problem is to be solved, government needs to rethink its role in housing finance, delink housing social assistance from finance markets, and turn its attention to fundamental supply side and urban governance issues.
Keywords: 330; Wohnungsversorgung; Immobilienfinanzierung; Kreditpolitik; Wohnungsbaupolitik; Wirkungsanalyse; Philippinen